Predictors of kidney function in a cohort of Mexican adults - Elva L Torrescano-de Labra; Lea A Cupul-Uicab; Paula Ramírez-Palacios; Jorge Salmerón; Carmen P Muñoz-Aguirre; Eduardo Salazar-Martínez (Instituto Nacional de Salud Pública, 2020)
Objectives. Our aim was to examine prospectively predictors of subclinical renal alterations among adults without chronic kidney disease. Materials and methods. We analyzed data from a cohort of Mexican adults (n=757). Kidney function (2010) was assessed with the estimated glomerular filtration rate (eGFR-Cr), serum creatinine and uric acid. Predictors of each kidney function marker (2004) were identified with linear and logistic regression models. Results. 33% had an eGFR-Cr <90 ml/min/1.73 m2. eGFR-Cr was lower among men, those >40 years old and users of antihypertensive medication; and higher among those with a high protein intake. Serum creatinine predictors were similar to those observed for eGFR-Cr. Uric acid decreased in men, among those with obesity, hypertension and high cholesterol. Conclusion. Conventional kidney function biomarkers are useful to identify subclinical alterations. Some predictors of kidney function are potentially modifiable, therefore susceptible for intervention among high-risk groups.